Pengembangan Bahan Ajar Berbasis E-book Menggunakan Aplikasi Book Creator Pada Pembelajaran Pendidikan Pancasila Materi Aku Mengenal Indonesia Kelas I MI - Habibullah, Muhammad_Romadlon; Suyanti, Isnaeni (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The process of learning Pancasila education in class I at MI Islamiyah Tulungagung Baureno Bojonegoro. Material: I know Indonesia. Using learning resources in the form of textbooks or LKS books by conveying learning material is still monotonous, and rarely uses learning media during the learning process at school, thus making students feel bored and less enthusiastic about participating in the learning process of Pancasila education subjects. The research objectives are: 1). To describe the development of e-book based teaching materials using the book creator application in the material I got to know Indonesia in class 1 MI. 2). To describe the feasibility of e-book based teaching materials using the book creator application in the material I got to know Indonesia in class 1 MI . This research uses the R&D (Research and Development) research method, the ADDIE development model which consists of five stages which include analysis, design, development, implementation and evaluation. The results of the research show that this e-book-based teaching material is very suitable for use with the assessment results of media design experts 92%, language experts 90%, material experts 91%, student questionnaire responses 90%, and the average score of students in the pretest 84% and posttest 98%. So it can be concluded that there has been an increase in the ability to understand the material I know about Indonesia for class I MI students.